2019
DOI: 10.1101/843144
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of primer pairs for microbiome profiling across a food chain from soils to humans within the One Health framework

Abstract: 16The "One Health" framework emphasizes the ecological relationships between soil, plant, 17 animal and human health. Microbiomes play important roles in these relationships, as they 18 modify the health and performance of the different compartments and influence the transfer of 19 energy, matter and chemicals between them. Standardized methods to characterize 20 microbiomes along food chains are, however, currently lacking. To address this methodological 21 2 gap, we evaluated the performance of DNA extractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…S2). These values are well within the range of archaeal relative abundance estimates quantified with catalyzed reporter deposition fluorescence in situ hybridization (CARD-FISH) (Lloyd et al 2013), likely because V4 primers may not discriminate strongly against archaea (Wasimuddin et al 2019). Bacteria to archaea ratios, in particular those of the surface sediments at the deep stations (2.7±0.4, Fig.…”
supporting
confidence: 63%
“…S2). These values are well within the range of archaeal relative abundance estimates quantified with catalyzed reporter deposition fluorescence in situ hybridization (CARD-FISH) (Lloyd et al 2013), likely because V4 primers may not discriminate strongly against archaea (Wasimuddin et al 2019). Bacteria to archaea ratios, in particular those of the surface sediments at the deep stations (2.7±0.4, Fig.…”
supporting
confidence: 63%
“…3A). The primer pair used in this study can also amplify archaea (Wasimuddin et al, 2020) and we found Crenarchaeota and Euryarchaeota in Tomba degli Scudi (Fig. 3A).…”
Section: Subterranean Tombs That Are Highly Permissive For Lifementioning
confidence: 75%
“…These primers have been demonstrated to perform well for characterising the gut microbiota, however efficacy/performance for characterisation of the oral microbiota requires further investigation. A recent study showed a discrepancy in performance when applied to human gut versus skin microbiota [37]. Most studies of the saliva microbiota have employed primers which target the V2 variable region.…”
Section: Discussionmentioning
confidence: 99%